Unfinished business - Leyshon, Andrew (Sage, 2018)
This short commentary responds to James et al.’s report on the employment of economic geographers within in departments of business and management in UK universities. An initial ambivalence about the numbers of economic geographers working outside the sub-discipline has been replaced by growing concerns over the supply of early career economic geographers, the immediate pressures of the Research Excellence Framework and the growth and financial significance of business schools within the UK university sector. Collective action and collaboration by the remaining economic geographers is encouraged to stem the tide.